Clinical practice guidelines for the diagnosis of constipation-predominant irritable bowel syndrome and functional constipation in adults: a scoping review - Jingyuan Luo; Wing Lam Wendy To; Qianqian Xu; Jialing Zhang; Yanfang Ma; Sen Chow; Danny J. Yu; Chun-Su Yuan; Zhaoxiang Bian (BMC Gastroenterology)
Abstract Background Constipation-predominant irritable bowel syndrome (IBS-C) and functional constipation (FC) are prevalent disorders with overlapping and fluctuating symptoms, which pose challenges for accurate diagnosis. This study aimed to assess the consistency of diagnostic criteria for IBS-C and FC in adults across clinical practice guidelines (CPGs). Methods We conducted a scoping review of relevant CPGs by searching electronic databases (MEDLINE and CNKI) and the webpages of Health and Care Excellence (NICE), World Health Organization (WHO), World Gastroenterology Organization (WGO), the American College of Gastroenterology (ACG), American Gastroenterological Association (AGA), Chinese Society of Gastroenterology (CSGE) from Jan 2012 to July 2024. The included CPGs should contain the diagnostic criteria for IBS-C, FC, or both. Results We identified 27 CPGs, 14 for IBS-C diagnostic criteria, 9 for FC, and 4 for both IBS-C and FC. The Rome IV criteria were the most commonly applied by the included CPGs (59.3%), followed by the Rome III criteria (22.2%), and pathophysiology classification criteria (7.4%). Abdominal pain was emphasized in IBS-C CPGs (71.4%) but not in any FC CPGs, while spontaneous bowel movement (SBM) frequency was commonly used for FC (88.9%) but not mentioned in any IBS-C CPGs. While 40.7% CPGs acknowledged the similarity between IBS-C and FC, one CPG addressed abdominal pain intensity as a diagnostic criterion, using the 0–9 Likert scale to define painful constipation as a score greater than 4. 71.4% IBS-C CPGs recommended a positive symptom-based diagnosis, versus 11.1% of FC CPGs. Geographical differences were observed, Asian-based CPGs (14.3% of IBS-C CPGs and 11.1% of FC/IBS-C CPGs) recommended stool form type 3 on the Bristol Stool Form Scale (BSFS) and abdominal bloating as diagnostic features. 81.5% CPGs recommended colonoscopy based on alarm symptoms or age. Conclusion Inconsistent and regional variations of existing diagnostic criteria for IBS-C/FC were identified. Future improvements should focus on comprehensive characterizations of pain and constipation in both IBS-C and FC. Long-term advancements in understanding the underlying mechanisms, including gut microbiota and related metabolites, are essential for identifying objective biomarkers to improve differential diagnosis and reduce reliance on symptom-based criteria.